2017
DOI: 10.1371/journal.pone.0175642
|View full text |Cite
|
Sign up to set email alerts
|

Mini-G proteins: Novel tools for studying GPCRs in their active conformation

Abstract: Mini-G proteins are the engineered GTPase domains of Gα subunits. They couple to GPCRs and recapitulate the increase in agonist affinity observed upon coupling of a native heterotrimeric G protein. Given the small size and stability of mini-G proteins, and their ease of expression and purification, they are ideal for biophysical studies of GPCRs in their fully active state. The first mini-G protein developed was mini-Gs. Here we extend the family of mini-G proteins to include mini-Golf, mini-Gi1, mini-Go1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
300
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(304 citation statements)
references
References 50 publications
(100 reference statements)
4
300
0
Order By: Relevance
“…To increase Gs coupling, membrane of cells expressing Cys‐CRF1R mutants were treated with recombinant mini‐Gs; a truncated variant of Gαs . It has been shown that GPCRs bound to mini‐Gs proteins adopt similar active‐state conformations as those of Gs‐protein bound receptors . Indeed, yields of crosslinking on ClAc‐ligand/Cys‐CRF1R pairs increased by increasing the concentration of mini‐Gs in the probes (Figure A).…”
Section: Resultssupporting
confidence: 73%
“…To increase Gs coupling, membrane of cells expressing Cys‐CRF1R mutants were treated with recombinant mini‐Gs; a truncated variant of Gαs . It has been shown that GPCRs bound to mini‐Gs proteins adopt similar active‐state conformations as those of Gs‐protein bound receptors . Indeed, yields of crosslinking on ClAc‐ligand/Cys‐CRF1R pairs increased by increasing the concentration of mini‐Gs in the probes (Figure A).…”
Section: Resultssupporting
confidence: 73%
“…In this work we used a construct of A 2A R that contained thioredoxin at the N-terminus of the receptor 26 . This was originally designed with a rigid linker between the thioredoxin and the receptor to generate a large hydrophilic surface to A 2A R to improve crystallisation, although this proved unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of thioredoxin did not significantly affect the pharmacology of A 2A R, as assessed by determination of its apparent K D for the inverse agonist ZM241385 or in agonist shift assays (Figure 1). It could also be purified to homogeneity and coupled effectively to both mini-G S 26 and to the heterotrimer containing mini-G S , β 1 , γ 2 and Nb35 (Figure 1). Detergent-solubilised A 2A R coupled to the heterotrimer had a molecular weight (excluding the detergent micelle of LMNG) of approximately 130 kDa 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus we focused on mini-G (mG) proteins, engineered versions of the Ras-like domain of G protein alpha subunits which bind directly to activated GPCRs but are not known to engage other cellular proteins 31,34 . We assessed binding to receptors in intact cells by redistribution of fluorescently labeled Nb or mG fusion proteins from the cytoplasm to the plasma membrane ( Figure 1B).…”
Section: Comparative Detection Of Direct Protein Recruitment By Opioimentioning
confidence: 99%